Global, regional, and national burden of chlamydial infection: a systematic analysis of incidence, prevalence, deaths, and DALYs with projections to 2046 - Hu, Jixu; Lan, Yanni; Zhang, Danyan; Lan, Guipeng; Wei, Jiyong (Frontiers in Public Health, 2025)
BackgroundChlamydial infection, a major sexually transmitted disease caused by Chlamydia trachomatis, imposes a substantial global health burden with uneven distribution. This study aims to quantify its global, regional, and national burden and project trends to 2046.MethodsData from the Global Burden of Disease (GBD) 2021 study were analyzed. We estimated 2021 burden metrics, evaluated temporal trends from 1990 to 2021 using estimated annual percentage changes (EAPC), and projected trends for 2022–2046 using an age-period-cohort (APC) model.ResultsIn 2021, global incidence was 235.7 million [95% uncertainty intervals (UI): 172.9–334.7 million] with an age-standardized incidence rate (ASIR) of 2902.13/100,000; prevalence was 152.2 million [113.2–213.0 million; age-standardized prevalence rate (ASPR): 1874.56/100,000]. There were 1,033 deaths [683–1,370; age-standardized deaths rate (ASDR): 0.01/100,000] and 163,617 disability-adjusted life-years (DALYs) [116,493–227,160; age-standardized DALYs rate (ASDAR): 2.01/100,000]. Geographic disparities were striking: Southern Sub-Saharan Africa and Central Asia had the highest ASIR, while Western Europe and High-income North America had the lowest. Asia bore the largest absolute burden. Males showed higher incidence rates, while females experienced higher prevalence, deaths, and DALYs. Temporal trends (1990–2021) showed fluctuating case counts and declining age-standardized rates (ASRs), with regional variations. Projections to 2046 indicate divergent sex-specific trends, with rising female ASIR/ASPR but declining absolute cases among males.ConclusionChlamydial infection exhibits marked global disparities, necessitating targeted interventions including region-specific strategies and gender-responsive care to reduce its burden.